Computational Studies of Solubilities of LiO2 and Li2O2 in Aprotic Solvents. Issue 11 (12th August 2017) - Cheng, Lei; Redfern, Paul; Lau, Kah Chun; Assary, Rajeev S.; Narayanan, Badri; Curtiss, Larry A.
Abstract : Knowledge of the solubilities of Li2 O2 and LiO2 in aprotic solvents is important for insight into the discharge and charge processes of Li-O2 batteries, but these quantities are not well known. In this contribution, the solvation free energies of molecular LiO2 and Li2 O2 in various organic solvents were calculated using various explicit and implicit solvent models, as well as ab initio molecular dynamics (AIMD) methods. The solvation energies from these calculations along with calculated lattice energies of Li2 O2 and LiO2 were used to determine the solubility of bulk LiO2 and Li2 O2 . The computed solubility of LiO2 (1.8 × 10 −2 M) is about 15 orders higher than that of Li2 O2 (2.0 × 10 −17 M) due to a much less negative lattice energy of bulk LiO2 compared to that of Li2 O2 . The difference in solubilities between LiO2 and Li2 O2 likely will affect the nucleation and growth mechanisms and resulting morphologies of the products formed during battery discharge, influencing the performance of the battery cell. The calculated LiO2 and Li2 O2 solubilities provide important information for fundamental studies of discharge and charge chemistries in Li-O2 batteries.